Environmental media exert a bottleneck in driving the dynamics of antibiotic resistance genes in modern aquatic environment. (1st October 2019) - Chen, Yihan; Li, Peng; Huang, Yuansheng; Yu, Kaifeng; Chen, Hongjie; Cui, Kangping; Huang, Qianli; Zhang, Junya; Yew-Hoong Gin, Karina; He, Yiliang
Abstract: With the rapid construction of dams worldwide, reservoir system has become a representation of modern aquatic environment. However, the profiles of antibiotic resistance genes (ARGs) and associated factor influencing their dynamics in modern aquatic environment (e.g., water phase, sediment phase, and soil phase) are largely unknown. Here, we comprehensively characterized the diversity, abundance, distribution of ARGs in a large drinking water reservoir using high-throughput quantitative PCR, as well as ranked the factors (e.g., mobile genetic elements (MGEs), bacteria community, bacterial biomass, antibiotics, and basic properties) influencing the profiles of ARGs on the basis of structural equation models (SEMs). Water phase was prone to harbor more diverse ARGs as compared to sediment phase and soil phase, and soil phase in drawdown area was a potential reservoir and hotspot for ARGs. Environmental media partially affected the ARG diversity in modern aquatic environment, while it observably influenced the distributions of ARGs and MGEs and their co-occurrence patterns. The pathways for the proliferation and spread of ARGs in water phase were both the horizontal gene transfer (HGT) and vertical gene transfer (VGT), while the dominant pathways in sediment phase and soil phase were the HGT and VGT, respectively. The SEMs demonstrated that MGEs contributed the most to drive the ARG dynamics in both water phase and sediment phase, while the most dominant factor for this in soil phase was bacterial community. Overall, environmental media exerted a bottleneck in driving the dynamics of ARGs in modern aquatic environment probably via diversifying the MGEs, bacterial community, bacterial biomass, antibiotics and basic properties. Graphical abstract: Image 1 Highlights: Soil phase in drawdown area is a potential pool and hotspot for ARGs. Environmental media significantly influenced the distributions of ARGs and MGEs. Environmental media could alter the dominant ways in increasing the absolute abundance of ARGs. MGEs contributed the most to shape the ARG dynamics both in water and sediment phases. The most dominant factor shaping the ARG dynamics in soil phase was bacterial community.